Selected Aspects of Forest Economy in Poland in the Regional Level (Research Bulletins of the Faculty of Economic Sciences, 2018)
The necessity to implement sustainable forest management is associated with a complex approach to forest resources. These resources are not only production functions, but also ecological and social ones. The aim of the research is an attempt to assess environmental aspects of forest management and economic assessment of the use of forests in voivodships in Poland. The study is based on the assessment of. Data comes from the Local Data Bank and Data Bank on Forests (base year - 2016). Both analyzes were based on the synthetic indicator non-pattern method. Both synthetic measures were compiled in a matrix to investigate the relationship between them. A positive relationship was obtained. Voivodeships characterized by a higher level of natural aspects of forest management are also characterized by a higher level of economic use of forest resources. Regions with low values of the level of natural aspects use the economic capabilities of forests to a fairly low extent.
Keywords: forest, forest management, regional analysis